A Response to "Arguments Against the Core Area Hypothesis" for Plant Domestication. (20th October 2013) - Gopher, Avi; Lev-Yadun, Simcha; Abbo, Shahal
Abstract : The paper relates to several issues concerning geographical and chronological aspects of the 'core area' model for plant domestication in the Levant (LevYadun et al. 2000), as presented in Fuller et al. (2011). The paper stresses that the core area as depicted by Fuller et al. does not correspond to the original core area map and list of Neolithic sites published by the authors (Lev-Yadun et al. 2000). It also discusses the alternative model suggested by Fuller et al., namely the alleged existence of autonomous, independent domestication centres in the Levant, a suggestion that does not conform to the available archaeobotanical, as well as genetic and archaeological data. A primarily technical section on chronology considers the procedures used by Fuller and his associates concerning 14 C dating. Archaeobotanical data inconsistencies are also noted.